2015
DOI: 10.1103/physrevd.92.036012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the inverse magnetic catalysis and the vector interaction in the location of the critical end point

Abstract: The effect of a strong magnetic field on the location of the critical end point (CEP) in the QCD phase diagram is discussed under different scenarios. In particular, we consider the contribution of the vector interaction and take into account the inverse magnetic catalysis obtained in lattice QCD calculations at zero chemical potential. The discussion is realized within the (2 þ 1) Polyakov-Nambu-Jona-Lasinio model. It is shown that the vector interaction and the magnetic field have opposite competing effects,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 104 publications
(146 reference statements)
5
25
0
Order By: Relevance
“…[27,29,46]. The main conclusions when μ u ¼ μ d ¼ μ s were that the trend is similar for both models: as the intensity of the magnetic field increases until a certain value (eB ∼ 0.4 GeV 2 [27,29]), the transition temperature increases and the baryonic chemical potential decreases. For even stronger magnetic fields, when no inverse magnetic catalysis (IMC) effects are considered, both T CEP and μ CEP B increase [27,46].…”
Section: The Influence Of the Magnetic Field On The Isentropic Tramentioning
confidence: 87%
See 4 more Smart Citations
“…[27,29,46]. The main conclusions when μ u ¼ μ d ¼ μ s were that the trend is similar for both models: as the intensity of the magnetic field increases until a certain value (eB ∼ 0.4 GeV 2 [27,29]), the transition temperature increases and the baryonic chemical potential decreases. For even stronger magnetic fields, when no inverse magnetic catalysis (IMC) effects are considered, both T CEP and μ CEP B increase [27,46].…”
Section: The Influence Of the Magnetic Field On The Isentropic Tramentioning
confidence: 87%
“…[28] and more recently in Ref. [29], where the presence of an external magnetic field was also considered. It was shown that the CEP can be absent in the phase diagram when the value of the coupling G V is greater than the critical value of G crit V ≈ 0.71G S within the present parametrization [29].…”
Section: B Results At G V ≠ 0: the Influence Of The Vector Interactimentioning
confidence: 99%
See 3 more Smart Citations